Health and safety implementation in Indonesia and risk of COVID-19 - Adithya Sudiarno; Sri Indriyani Diartiwi; Ratna Sari Dewi; M. Rizqi Zulqornain; Maria Susanti; Edwin Hermawan; Dedy Dedy; Syamsul Arifin; Reni Wulansari; Reza Aulia Akbar; Muhammad Hendrawan Hidayat; Rico Feryanto (Intelektual Pustaka Media Utama, 2021)
The COVID-19 pandemic impacted the socio-economic sectors since the end of 2019. Indonesian’s Government issued the large-scale social restrictions policy to limit the industrial activities. This study aimed to investigate the difference of the health, safety, and environment (HSE) implementations among Indonesian companies, before and during the disruption risk of COVID-19 pandemic according to the use of personal protective equipment (PPE). It used a random sampling, involved 1,027 workers from various sectors of Indonesian companies. Hypothesis tests used are ANOVA and t-test method. The level of HSE compliance changed quite significantly when the COVID-19 outbreak emerged. The results explained, there is no significant difference in HSE compliance based on company location, company risk level, and position of a respondent in the company. However, there is a significant difference between companies that have a HSE division and a HSE Management System certificate with the company who did not have any. The recommendations of HSE improvement formulated using a Safety Model Canvas and a Focus Group Discussion conducted to convey the jazz scenario in the next normal. This study suggests the priority order for HSE improvement strategy in a company is commitment, responsibility, engagement and involvement, leadership, competence, information and communication, to organizational learning.